Assessment of Ganoderma infection in oil palm (Elaeis guineensis jacq.) by pre-inoculation of arbuscular mycorrhiza fungi and endophytic bacteria. - Sundram, Shamala (2012)
Basal stem rot of oil palm (Elaeis guineensis Jacq.) caused by Ganoderma spp is of major economic concern and it is the predominant disease of oil palm in Southeast Asia. The disease is a “white rot” process involving growth of the fungus within the oil palm as the lignin and cellulose are biodegraded. There is yet an effective measure to control the disease. Endophytic microorganisms such as arbuscular mycorrhizal fungi (AMF) and endophytic bacteria (EB) have been previously identified as potential biocontrol agents especially for soil borne diseases. These endophytes are able to suppress diseases with various mechanisms such as antibiosis, lysis, and production of antifungal compounds and induced systemic resistance (ISR). The use of endophytes is also preferred as they reside within the plant system avoiding rhizosphere competence such as competition for space and nutrient between other soil microbes. Therefore this study was designed with the specific objectives to (i) investigate the antagonistic potential and compatibility between both endophytes, (ii) explore the potential disease suppression and vegetative growth enhancement in pre-inoculated oil palm seedlings challenged with G. boninense, (iii) determine the biochemical responses and gene expression profile in pre-inoculated seedlings challenged with G.boninense, and (iv) evaluate the effect of single and a consortium of endophytic microorganisms in field trial using the seedling baiting technique. AMF (Glomus intraradices UT 126 and G. clarum BR152B)and EB (Pseudomonas strain UPMP3 and Burkholderia strain UPMB3)represent the endophytic microbes tested in this study. Symbiotic interactions were observed between AMF species; Glomus intraradices UT 126 and G. clarum BR152B with Pseudomonas strain UPMP3 and Burkholderia strain UPMB3. Both EB strains significantly increased germination and hyphal length of AMF spores by 180 to 240%,respectively. This is a novel finding as the EB strains were never reported as potential mycorrhizal helper bacteria (MHB). Antagonistic effect of EB strains was demonstrated by the percentage inhibition of radial growth of G. boninense at >86% and >74% by UPMP3 and UPMB3, respectively. Scanning electron micrographs revealed severe morphological deformities such as shrivelling, flattening and shrinking of G. boninense hyphae in the presence of UPMP3 and UPMB3 strains. In addition,production of POX, PPO, chitinase and β-1, 3-glucanase during pre and post infection were enhanced in pre-inoculated seedlings and reassessed with gene expression analysis. It is also proposed that PPO acts as a potential biomarker for induced resistance against G. boninense. The single application of UT126 (T2) was found to be superior in increasing the vegetative parameters such as height, girth, leaf area, frond count and fresh weight of leaf and root with significant difference at P<0.05. However, disease suppression was highest in treatment that had the application of both AMF and UPMP3 with a disease reduction of 57.53% (P<0.05). The disease incidence in treatment with both AMF and UPMP3 (T4) was delayed by 8 weeks indicating effective suppression of BSR infection. Similar treatments were subjected to field trial using seedling bait technique. Disease suppression in T4 was significantly highest with reduced disease severity of 4.33% (P<0.05) when compared to other treatments (ranging from 7 to 14% o infection), 20 months after planting. This is the first report of field seedling baiting technique to be successfully implemented in testing microbial pre-inoculation for disease suppression. Pre-inoculation with AMF and UPMP3 was most effective in reducing disease severity in oil palm either in nursery or field conditions.